PEMIKIRAN POLITIK ISLAM LIBERAL DAN PERKEMBANGANNYA DI INDONESIA DEWASA INI - Prayudi Prayudi (Jurnal Politica, 2013)
The dynamic of an Islam political thinking have a strategic role in the state affairs, with all their arguments which was followed in the implementation levels. One of among thatdevelop in the Indonesian landscape, is the proponent called as a Liberal Islamic political thinking. These stream proposed a freedom of an Islamic rationality idea which contradictwith the model of literal comprehension of Islam thinking. Their present is precisely become a specific political controversial in Indonesia where an effort to achieve towardconsolidation of democratic transition base on a road map who wants by a half of an elite and the majority of public. The important of substance from a debate in the Islamic liberalthinking has been marked with many things aspect, such as an issues of secularization in the one side and pluralism as an issues in the other side.